PhD EDUCATION QUALITY EVALUATION: EXPERIENCE OF UNIVERSITIES OF LITHUANIA AND FINLAND - Iryna Lynova (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article suggests an overview and analysis of the principles and procedures of quality assurance in higher education and quality assessment of PhD study in Ukraine in the context of European integration. The leading international experience on the research topic for which we have selected universities of the partner countries Lithuania and Finland cooperating with the Institute of Higher Education in international projects is presented. The international experience on quality assessment of PhD study is presented by an analysis of the official documents available in English on the Lithuanian and Finnish universities' websites in open access. The presented leading experience of the European universities have shown that the issue of quality assessment of doctoral programmes and study is considered as a part of the overall quality assessment in higher education and is not single out as a separate procedure. In case of absence of mandatory accreditation of educational programmes in higher education in Finland, a system of auditing the content and correspondence of the internal system of quality assurance in higher education institution, but not of separate educational programmes for PhD students, is in place. The responsibility for quality in PhD education is shared between a PhD student, supervisor and university structural units when their particular roles and functions are exceptionally important.